2005
DOI: 10.1073/pnas.0503733102
|View full text |Cite
|
Sign up to set email alerts
|

Selection of ribozymes that catalyse multiple-turnover Diels–Alder cycloadditions by using in vitro compartmentalization

Abstract: In vitro compartmentalization (IVC) has previously been used to evolve protein enzymes. Here, we demonstrate how IVC can be applied to select RNA enzymes (ribozymes) for a property that has previously been unselectable: true intermolecular catalysis. Libraries containing 10 11 ribozyme genes are compartmentalized in the aqueous droplets of a water-in-oil emulsion, such that most droplets contain no more than one gene, and transcribed in situ. By coencapsulating the gene, RNA, and the substrates͞products of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 46 publications
0
90
0
4
Order By: Relevance
“…Since their initial description (2,3), aptamers have been discovered for a wide variety of molecular targets including small molecules (2), proteins (3)(4)(5), cell surfaces (6), whole organisms (7), and inorganic materials (8), and they have matured as a useful tool for disease diagnostics and therapeutics as well as basic research (9)(10)(11)(12)(13)(14). Once the nucleic acid sequence of the aptamer is identified for a particular target, it is produced synthetically-a distinct advantage over traditional affinity reagents such as antibodies, which require biological processes (e.g., hybridoma).…”
mentioning
confidence: 99%
“…Since their initial description (2,3), aptamers have been discovered for a wide variety of molecular targets including small molecules (2), proteins (3)(4)(5), cell surfaces (6), whole organisms (7), and inorganic materials (8), and they have matured as a useful tool for disease diagnostics and therapeutics as well as basic research (9)(10)(11)(12)(13)(14). Once the nucleic acid sequence of the aptamer is identified for a particular target, it is produced synthetically-a distinct advantage over traditional affinity reagents such as antibodies, which require biological processes (e.g., hybridoma).…”
mentioning
confidence: 99%
“…Inspired by the natural model of cellular compartmentalisation, Agresti et al (2005) developed a system termed in vitro compartmentalization (IVC). IVC uses compartmentalization to link genotype (a nucleic acid that can be replicated) and phenotype (a functional trait such as a binding or catalytic activity).…”
Section: Concluding Remar Ksmentioning
confidence: 99%
“…In fact the Diels-Alder reaction catalyzed by DNA, which may further indicate the general nature of the requirement for hydrophobic surfaces to bring the diene and dienophile together [46]. However, in the case of the RNA J49, the specificity of binding by the hydrophobic effect reveals a second major issue in the development of artificial ribozymes, namely product inhibition [70].…”
Section: Effect Of Hydrophobic Interactions On Ribozyme Catalysismentioning
confidence: 99%
“…While this is an excellent example of the power of in vitro selection, the tight binding of the product, rather than the transition state, shows that product inhibition is an inherent problem for the tethered substrate selection strategy [72]. It was later shown that product inhibition can be potentially overcome with appropriate selection design using an in vitro compartmentalization strategy [70]. In this strategy the reaction takes place under multiple turnover conditions in a single droplet so that selection of a true enzyme can be accomplished.…”
Section: Effect Of Hydrophobic Interactions On Ribozyme Catalysismentioning
confidence: 99%